PERANAN PENDIDIKAN BAGI PENGEMBANGAN PERADABAN DALAM PANDANGAN FUKUZAWA YUKICHI - Rukiyati Rukiyati (Jurnal Kependidikan, 2000)
The study was designed to describe the philosophical concept of education according ta Fukuzawa, especially his thought about the role of education  for  development of civilization. This study was a library research by high lighting a concept  from  a prominent  The data consisted of both the primary and secondary data. The primary data were Fulauawa's writing taken from  figure. this three boola: An Encouragement of Learning; Fulanawa Yudchi on Education: elected Worla; and An Outline of a Theory of Civilization. Secondary data were taken  from others expert's worlcs qbout Fuhtzawa. The method of this study was the philosophical hermeneutic method with interpretation, holistic, descriptive elements. The conclusion of this study are: (I) the role of education according to Fulauawa is the main way to reach the civilized of modern societli (2) the civilization spirit in identified by Fulauawa as the spirit to pursue and appreciate lmowledge and science and to realize virtue's value.